CTA Project Completion Report: Building capacity for institutionalizing food safety tracking in the African Union Member States - Ayalew, Amare; Visser, Piet (Technical Centre for Agricultural and Rural Cooperation, 2020)
Recognizing the importance of addressing the challenges of unsafe food, the Africa Union Commission (AUC) and the Technical Center for Rural Development Agriculture (CTA) launched a project titled “Building Capacity for Institutionalizing Food Safety Tracking in the African Union Member States” in December 2018. In line with its objective, the project successfully developed the Africa Food Safety Index (AFSI) in consultation with food safety experts from relevant institutions within and outside Africa. AFSI is a composite index that attempts to capture the multi-sectoral nature and impacts of food safety through a simple set of indicators of food safety policy, health, and trade. AFSI was endorsed by technical experts and member state officials to be integrated in the Comprehensive Africa Agriculture Development Programme (CAADP) biennial reporting (BR) mechanism, which presents performance of countries in meeting targets of the Malabo Declaration for Agricultural Transformation. Led by the AUC and with the active engagement of technical partners such as the International Livestock Research Institute (ILRI) and the Food and Agriculture Organization of the United Nations (FAO), AFSI undergone a round of technical reviews and political consultation processes that involved Regional Economic Communities (RECs), member states and other partners. The project sensitized policy makers on the challenges of unsafe food, its linkage to the economy and the health sector, as well as the use of evidence for decision making. In addition to project specific events, PACA used its participation in different policy relevant forums to consult policy makers and advocate for tracking food safety indicators through the BR mechanism for. These consultative actions enhanced awareness of policy makers about the importance of food safety and generated ownership for reporting on AFSI.